Packaging slurry and preparation method and application thereof

By optimizing the composition of glass powder and introducing specific carrier materials and additives, the water absorption problem of traditional packaging slurry in humid environments is solved, and the water resistance of packaging slurry is significantly improved, which is suitable for packaging and protection of high-performance electronic devices.

CN119707301AActive Publication Date: 2025-03-28XIAN TENGXING ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202510227965.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

Traditional packaging slurry is prone to absorb water in humid environments, affecting the electrical performance and long-term reliability of electronic devices.

Method used

By selecting the appropriate glass components, introducing specific carrier materials and additives, and combining with an optimized preparation process, a more stable and dense glass phase structure is formed to improve the water resistance of the encapsulating slurry.

Benefits of technology

The water resistance of the packaging slurry is significantly improved, forming a more uniform packaging layer, enhancing the cohesion of the packaging layer, and effectively improving the water resistance of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic packaging, and relates to packaging slurry and a preparation method and application thereof. The invention provides a packaging slurry, the packaging slurry comprises glass powder and a carrier, the glass powder is composed of SiO2, B2O3, Al2O3, PbO, MgO and SrO, and the carrier is composed of SiO2, B2O3, Al2O3, PbO, MgO and SrO. The preparation method of the carrier comprises the following steps: mixing nano zirconium dioxide and an additive according to a mass ratio of 0.5: (1-2), and blending in a mixer for 3-5 hours, thereby obtaining the carrier, the additive is prepared from isooctyl acetate, gamma-aminopropyl trimethoxy silane, propylene glycol polyether and butyl carbitol acetate. The packaging slurry can improve the water resistance of the electronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic packaging and relates to a packaging slurry and a preparation method and application thereof. Background Art

[0002] In the field of electronic packaging technology, packaging paste, as a key material, plays a vital role in the performance and reliability of electronic devices. Traditional packaging paste usually contains glass powder and organic carrier, which is used to achieve the connection and protection between electronic components and substrates.

[0003] Although traditional encapsulation pastes meet the needs of electronic packaging to a certain extent, they are still insufficient in terms of water resistance. This is mainly due to the fact that the composition of the glass powder and the properties of the carrier are not optimized enough, which makes the encapsulation layer easy to absorb water in a humid environment, thus affecting the electrical performance and long-term reliability of electronic devices. In addition, traditional carrier materials often contain easily hydrolyzed components, which further aggravates the water resistance problem of the encapsulation layer.

[0004] Therefore, it is necessary to improve the formulation and preparation process of the encapsulation slurry to improve its water resistance. Summary of the invention

[0005] The present invention proposes a new encapsulation slurry and a preparation method thereof, aiming to solve the problems existing in the prior art. The encapsulation slurry of the present invention significantly improves the water resistance of the encapsulation slurry by selecting a suitable glass component, introducing a specific carrier material and additives, and combining an optimized preparation process. The present invention provides a new solution for the encapsulation and protection of electronic devices.

[0006] To achieve the above object, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a packaging paste, wherein the packaging paste comprises glass powder and a carrier, wherein: The glass powder consists of SiO2, B2O3, Al2O3, PbO, MgO and SrO; The preparation method of the carrier is as follows: nano zirconium dioxide and additives are mixed in a mass ratio of 0.5:1-2, and then placed in a mixer and blended for 3-5 hours to obtain the carrier; The additive consists of isooctyl acetate, gamma-aminopropyltrimethoxysilane, propylene glycol polyether and butyl carbitol acetate.

[0007] Preferably, the encapsulation slurry comprises 41-46 parts of glass powder and 30-36 parts of carrier in parts by mass.

[0008] Preferably, in terms of mass fractions, the glass powder consists of 28-32 parts of SiO2, 10-12 parts of B2O3, 16-22 parts of Al2O3, 5-8 parts of PbO, 3-6 parts of MgO and 1-3 parts of SrO.

[0009] Preferably, in terms of parts by mass, the additive consists of 0.5-1 part of isooctyl acetate, 1-2 parts of γ-aminopropyltrimethoxysilane, 0.4-0.8 parts of propylene glycol polyether and 0.2-0.5 parts of butyl carbitol acetate.

[0010] More preferably, in terms of mass fractions, the glass powder consists of 31 parts of SiO2, 11 parts of B2O3, 20 parts of Al2O3, 6 parts of PbO, 5 parts of MgO and 2 parts of SrO.

[0011] More preferably, the additive consists of 0.6 parts of isooctyl acetate, 1 part of γ-aminopropyltrimethoxysilane, 0.6 parts of propylene glycol polyether and 0.3 parts of butyl carbitol acetate in parts by mass.

[0012] Preferably, the preparation method of the carrier is: mixing nano zirconium dioxide and additives in a mass ratio of 0.5:1, placing the mixture in a mixer and blending for 3-5 hours.

[0013] In a second aspect, a method for preparing the encapsulation slurry according to the present invention is provided, the preparation method comprising the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1200°C for 1.5-3h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of carrier: Mix nano zirconium dioxide and additives in a mass ratio of 0.5:1-2, place in a mixer and blend for 3-5 hours; 3) Preparation of slurry: At a temperature of 65-80°C, the glass powder and the carrier are evenly dispersed by ultrasonic to obtain encapsulation slurry.

[0014] In a third aspect, a slurry with good water resistance is provided, wherein the slurry includes the encapsulation slurry described in the present invention.

[0015] In a fourth aspect, there is provided application of the encapsulation slurry of the present invention in improving the water resistance of electronic devices.

[0016] A fifth aspect provides application of the slurry of the present invention in improving the water resistance of electronic devices.

[0017] Compared with the prior art, the beneficial effects of the present invention are: The present invention significantly improves the water resistance of the encapsulation slurry by introducing specific carrier materials and additives, optimizing the glass powder composition and preparation process, and is suitable for the encapsulation and protection of high-performance electronic devices. Specifically, The present invention can form a more stable and dense glass phase structure by accurately controlling the ratio of SiO2, B2O3, Al2O3, PbO, MgO and SrO in the glass powder. This structure has lower water absorption and better moisture resistance, thereby effectively improving the water resistance of the encapsulation layer. The addition of PbO can also adjust the softening point and viscosity of the glass phase, which helps to form a more uniform encapsulation layer, thereby further reducing the water absorption of the glass phase structure.

[0018] The invention uses nano zirconium dioxide in combination with an additive consisting of isooctyl acetate, γ-aminopropyl trimethoxysilane, propylene glycol polyether and butyl carbitol acetate to enhance the interfacial bonding between nano zirconium dioxide and other materials in the electronic device, thereby improving the stability and water resistance of the overall structure. It can also form a dense protective layer on the surface of the electronic device to effectively prevent water penetration and erosion.

[0019] In addition, the additive of the present invention not only helps to reduce the viscosity of the carrier and improve the dispersibility of the carrier, but also forms a stronger interaction with the glass powder, enhances the cohesive force of the encapsulation layer, and helps to further improve the water resistance of the encapsulation layer.

[0020] Furthermore, the present invention can ensure that the encapsulation slurry has the best composition and performance by precisely controlling the melting temperature and time of the glass powder, the blending conditions of the carrier and the dispersion temperature of the slurry. In particular, the application of the ultrasonic dispersion step can further refine the particle size of the glass powder and the carrier, improve the uniformity and stability of the slurry, and thus facilitate the formation of a more dense and uniform encapsulation layer, thereby improving water resistance. DETAILED DESCRIPTION

[0021] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0022] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0023] Example 1 This embodiment provides a packaging slurry, which includes 41 parts of glass powder and 30 parts of carrier in terms of mass fraction, wherein: The glass powder is composed of 28 parts of SiO2, 10 parts of B2O3, 16 parts of Al2O3, 5 parts of PbO, 3 parts of MgO and 1 part of SrO; The preparation method of the carrier is as follows: nano zirconium dioxide and additives are mixed in a mass ratio of 0.5:1, and then placed in a mixer and blended for 3 hours; The additive consists of 0.5 parts of isooctyl acetate, 1 part of gamma-aminopropyltrimethoxysilane, 0.4 parts of propylene glycol polyether and 0.2 parts of butyl carbitol acetate.

[0024] Example 2 This embodiment provides a packaging slurry, which includes 46 parts of glass powder and 36 parts of carrier in terms of mass fraction, wherein: The glass powder is composed of 32 parts of SiO2, 12 parts of B2O3, 22 parts of Al2O3, 8 parts of PbO, 6 parts of MgO and 3 parts of SrO; The preparation method of the carrier is as follows: nano zirconium dioxide and additives are mixed in a mass ratio of 0.5:2, placed in a mixer and blended for 5 hours; The additive consists of 1 part of isooctyl acetate, 2 parts of gamma-aminopropyltrimethoxysilane, 0.8 parts of propylene glycol polyether and 0.5 parts of butyl carbitol acetate.

[0025] Example 3 This embodiment provides a packaging slurry, which includes 43 parts of glass powder and 32 parts of carrier in terms of mass fraction, wherein: The glass powder is composed of 31 parts of SiO2, 11 parts of B2O3, 20 parts of Al2O3, 6 parts of PbO, 5 parts of MgO and 2 parts of SrO; The preparation method of the carrier is as follows: nano zirconium dioxide (Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., 1314-23-4) and additives are mixed in a mass ratio of 0.5:1, and the mixture is placed in a mixer and blended for 4 hours to obtain the carrier.

[0026] The additive consists of 0.6 parts of isooctyl acetate, 1 part of gamma-aminopropyltrimethoxysilane, 0.6 parts of propylene glycol polyether and 0.3 parts of butyl carbitol acetate.

[0027] Example 4 This embodiment provides a method for preparing a packaging slurry, the preparation method comprising the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1200°C for 1.5-3h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of carrier: Mix nano zirconium dioxide and additives in a mass ratio of 0.5:1-2, place in a mixer and blend for 3-5 hours; 3) Preparation of slurry: At a temperature of 65-80°C, the glass powder and the carrier are evenly dispersed by ultrasonic to obtain encapsulation slurry.

[0028] Comparative Example 1 This comparative example is the same as Example 3, except that isooctyl acetate in the additive is replaced by ethyl acetate.

[0029] Comparative Example 2 This comparative example is the same as Example 3, except that the mass ratio of nano zirconium dioxide to the additive is adjusted to 0.5:0.5.

[0030] Comparative Example 3 This comparative example is the same as Example 3, except that the nano zirconium dioxide is replaced by zirconium dioxide.

[0031] Effect verification Experimental objects: encapsulation slurries prepared according to Example 4 in Examples 1-3 and Comparative Examples 1-3; Experimental methods: The above encapsulation slurries were screen-printed on 1206 aluminum oxide substrates, dried at 140°C for 15 minutes, and then cured at 200°C for 30 minutes to make samples. The samples were then completely immersed in 95°C distilled water (pure and free of impurities) for 96 hours, and the water resistance loss value was calculated. Experimental results: as shown in Table 1.

[0032] Table 1 Water resistance test results of each group of samples

[0033] In order to further demonstrate the effect of the present invention, the γ-aminopropyltrimethoxysilane, propylene glycol polyether and butyl carbitol acetate in the additives are replaced by other substances with similar properties, and the other conditions are consistent with those in Example 3. The results show that the effect is equivalent to that of Comparative Example 1.

[0034] In order to further demonstrate the effect of the present invention, the mass ratio of nano zirconium dioxide and additives in the present embodiment is adjusted to 0.5:2.5, and the other conditions are consistent with those in Example 3. The results show that the effect is equivalent to that in Comparative Example 2. As shown in Table 1, the water resistance of each group of samples made of the encapsulation slurry of the present invention is relatively good, all below 0.1, among which the water resistance of the sample of Example 3 is the best; while the water resistance of each group of samples of Comparative Examples 1-3 is relatively poor. Therefore, compared with the encapsulation slurry without the formulation system of the present invention, the encapsulation slurry using the formulation system of the present invention can be well used for the encapsulation and protection of high-performance electronic devices.

[0035] It can be seen from the effect verification experiment that the present invention significantly improves the water resistance of the encapsulation slurry by introducing specific carrier materials and additives and optimizing the glass powder composition and preparation process. The present invention is suitable for the encapsulation and protection of high-performance electronic devices.

[0036] The present invention can form a more stable and dense glass phase structure by accurately controlling the ratio of SiO2, B2O3, Al2O3, PbO, MgO and SrO in the glass powder. This structure has lower water absorption and better moisture resistance, thereby effectively improving the water resistance of the encapsulation layer. The addition of PbO can also adjust the softening point and viscosity of the glass phase, which helps to form a more uniform encapsulation layer, thereby further reducing the water absorption of the glass phase structure.

[0037] The invention uses nano zirconium dioxide in combination with an additive consisting of isooctyl acetate, γ-aminopropyl trimethoxysilane, propylene glycol polyether and butyl carbitol acetate to enhance the interfacial bonding between nano zirconium dioxide and other materials in the electronic device, thereby improving the stability and water resistance of the overall structure. It can also form a dense protective layer on the surface of the electronic device to effectively prevent water penetration and erosion.

[0038] In addition, the additive of the present invention not only helps to reduce the viscosity of the carrier and improve the dispersibility of the carrier, but also forms a stronger interaction with the glass powder, enhances the cohesive force of the encapsulation layer, and helps to further improve the water resistance of the encapsulation layer.

[0039] Furthermore, the present invention can ensure that the encapsulation slurry has the best composition and performance by precisely controlling the melting temperature and time of the glass powder, the blending conditions of the carrier and the dispersion temperature of the slurry. In particular, the application of the ultrasonic dispersion step can further refine the particle size of the glass powder and the carrier, improve the uniformity and stability of the slurry, and thus facilitate the formation of a more dense and uniform encapsulation layer.

[0040] To sum up, the formula system of the encapsulation slurry provided by the present invention is a whole. Specifically, the raw materials in the encapsulation slurry support each other functionally and interact with each other. It is precisely because the raw materials support each other functionally and interact with each other that the encapsulation slurry of the formula system of the present invention has good water resistance.

[0041] It should be understood that the disclosed invention is not limited only to the specific method, scheme and material of description, because these all can change.It should also be understood that the terminology used herein is only for the purpose of describing specific embodiment scheme, rather than being intended to limit the scope of the present invention, and the scope of the present invention is only limited to the appended claims.

Claims

1. A packaging slurry, characterized in that: The encapsulation paste comprises glass powder and a carrier, wherein: The glass powder consists of SiO2, B2O3, Al2O3, PbO, MgO and SrO; The preparation method of the carrier is as follows: nano zirconium dioxide and additives are mixed in a mass ratio of 0.5:1-2, and then placed in a mixer and blended for 3-5 hours to obtain the carrier; The additive consists of isooctyl acetate, gamma-aminopropyltrimethoxysilane, propylene glycol polyether and butyl carbitol acetate.

2. The encapsulation paste according to claim 1, characterized in that: In terms of weight, the encapsulation paste includes 41-46 parts of glass powder and 30-36 parts of carrier.

3. The encapsulation paste according to claim 1, characterized in that: In terms of mass fractions, the glass powder consists of 28-32 parts of SiO2, 10-12 parts of B2O3, 16-22 parts of Al2O3, 5-8 parts of PbO, 3-6 parts of MgO and 1-3 parts of SrO.

4. The encapsulation paste according to claim 1, characterized in that: In terms of weight percentage, the additive consists of 0.5-1 part of isooctyl acetate, 1-2 parts of γ-aminopropyltrimethoxysilane, 0.4-0.8 parts of propylene glycol polyether and 0.2-0.5 parts of butyl carbitol acetate.

5. The encapsulation paste according to claim 3, characterized in that: In terms of mass fraction, the glass powder consists of 31 parts of SiO2, 11 parts of B2O3, 20 parts of Al2O3, 6 parts of PbO, 5 parts of MgO and 2 parts of SrO.

6. The encapsulation paste according to claim 4, characterized in that: In terms of mass parts, the additive consists of 0.6 parts of isooctyl acetate, 1 part of γ-aminopropyltrimethoxysilane, 0.6 parts of propylene glycol polyether and 0.3 parts of butyl carbitol acetate.

7. The encapsulation paste according to claim 1, characterized in that: The preparation method of the carrier is as follows: nano zirconium dioxide and additives are mixed in a mass ratio of 0.5:1, and the mixture is placed in a mixer and blended for 3-5 hours to obtain the carrier.

8. The method for preparing the encapsulation slurry according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: 1) Preparation of glass powder S11. After the components of the glass powder are evenly mixed, they are melted at a temperature of 1000-1200°C for 1.5-3h, quenched with water, and cooled to solidify; S12. The solidified mixture is successively crushed, ball-milled, sieved and dried to obtain a glass powder having a particle size of less than 5 μm; 2) Preparation of carrier: Mix nano zirconium dioxide and additives in a mass ratio of 0.5:1-2, place in a mixer and blend for 3-5 hours; 3) Preparation of slurry: At a temperature of 65-80°C, the glass powder and the carrier are evenly dispersed by ultrasonic to obtain encapsulation slurry.

9. A slurry with good water resistance, characterized in that: The slurry comprises the encapsulation slurry according to any one of claims 1 to 7.

10. Use of the encapsulation slurry according to any one of claims 1 to 7 or the slurry according to claim 9 in improving the water resistance of electronic devices.

Citation Information

Patent Citations

  • Slurry for preparation of glass fluorescent layer used for LED encapsulation

    CN102730974A

  • 3D packaging LTCC substrate material and preparation method

    CN105271758A

  • Microcrystalline glass capable of resisting high temperature of 650 DEG C and preparation method therefor

    CN106882923A

  • Composite glass slurry and preparation method thereof

    CN115466057A

  • Glass powder applied to dielectric paste and preparation method thereof

    CN116606074A

Cited By

  • Silica gel film for CSP and preparation method and application thereof

    CN120888270A